Zebrafish Model of Severe Combined Immunodeficiency (SCID) Due to JAK3 Mutation - Faiza Basheer; Effie Lee; Clifford Liongue; Alister C. Ward (Biomolecules, 2022)
JAK3 is principally activated by members of the interleukin-2 receptor family and plays an essential role in lymphoid development, with inactivating JAK3 mutations causing autosomal-recessive severe combined immunodeficiency (SCID). This study aimed to generate an equivalent zebrafish model of SCID and to characterize the model across the life-course. Genome editing of zebrafish jak3 created mutants similar to those observed in human SCID. Homozygous jak3 mutants showed reduced embryonic T lymphopoiesis that continued through the larval stage and into adulthood, with B cell maturation and adult NK cells also reduced and neutrophils impacted. Mutant fish were susceptible to lymphoid leukemia. This model has many of the hallmarks of human SCID resulting from inactivating JAK3 mutations and will be useful for a variety of pre-clinical applications.